Green fashion. ([2016]) - Gardetti, Miguel Ángel; Cobb, Kelly A (Kelly Ann), 1958-; Orzada, Belinda T; Koszewska, Malgorzata; Hustvedt, Gwendolyn; Meier, Erica Jane; Waliczek, Tina Marie; Hennigs, Nadine; Karampournioti, Evmorfia; Wiedmann, Klaus Peter; Pal, Rudrajeet; Lee, Kyung Eun; et al.
No abstract available